United Kingdom : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2001)
This Selected Issues paper analyzes the specialty about the cyclical expansion in the United Kingdom. The paper reviews the labor market data, wage inequality, and implications for inequality. The study examines the contributions of information and communications technologies investment to output and labor productivity growth in the United Kingdom. The paper provides a qualitative assessment of the impact of the appreciation of sterling on U.K. foreign trade, and its effects on competitiveness, and the sectoral composition of production.